The Randic Index of a Power Graph - VARLIOĞLU, NURŞAH MUTLU (Editura Bibliotheca-Bibliotheca Publ House, 2025)
In this study, the Randi & cacute; index of the power graph of a finite cyclic group was redefined by considering its identity and generators. Then, bounds were obtained for the Randi & cacute; index of the power graph in question by using the concepts of maximum degree, minimum and vertex.
Keywords: Power Graph